Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ð³Ð»Ð¸Ñ†ÐµÑ€Ð¸Ð½Ð°, ÑÑ‚Ð¸Ð»ÐµÐ½Ð³Ð»Ð¸ÐºÐ¾Ð»Ñ Ð½Ð° Ð¼Ð¾Ñ€Ñ„Ð¾Ñ„ÑƒÐ½ÐºÑ†Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ñ‹Ðµ Ñ…Ð°Ñ€Ð°ÐºÑ‚ÐµÑ€Ð¸ÑÑ‚Ð¸ÐºÐ¸ ÑÐ¿ÐµÑ€Ð¼Ð°Ñ‚Ð¾Ð·Ð¾Ð¸Ð´Ð¾Ð² ÑÐ¾Ð±Ð°Ðº Ð½Ð° Ñ€Ð°Ð·Ð½Ñ‹Ñ… ÑÑ‚Ð°Ð¿Ð°Ñ… ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð¸Ñ - Egorov, M. I.; Kopeika, E. F.; Linnik, T. P.; Kuchkov, I. N. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
There has been studied the effect of glycerol and ethylene glycol (EG) on survival of dogsâ€™ spermatozoa (DS) after freeze-thawing depending on the concentration of cryoprotectants, cooling regimens and equilibration time, as well as the change in DS cell volume after the cryoprotectants being introduced into suspension by means of turbidimetric method. The highest motility of DS was revealed after cryopreservation under EG protection with final concentration of 7% when being frozen at the first stage with the rate of 3Â°C/min with no preliminary equilibration. It has been shown that 7% EG causes quite less alterations in cell volume if compared to glycerol.